Faktor-Faktor Risiko Terjadinya Epilepsi pada Anak di RSUD Dr. Moewardi - Paramita Riski Setianingsih; Agus Soedomo; Annang Giri Moelyo (Fakultas Kedokteran Universitas Sebelas Maret Surakarta, 2013)
Background: There is no definite epidemiological data about the number of patients with epilepsy in Indonesia. It is estimated that there are 900.0001.800.000 epilepsy patients. The onset can be at any age, in which 3032.9% patients experience the first convulsion less than 4 years old, 50-51.5% in less than 10 years old, 7583.5% in less than 20 years old, 15% in more than 25 years old and 2% in more than 50 years old. Several risk factors cause epilepsy in children e.g. hereditary factor, asphyxia, premature, complex febrile seizure and head trauma. Methods: This was a case control study. Subject were selected consecutively from epilepsy children in Dr. Moewardi Hospital and matched with pediatric patients in Outpatlient Pediatric Clinics. The data was collected by structured interview and medical record. The data analyzed by Chi-Square test and Logistic Regression. All statistic analysis was measured by Statistical Product and Service Solution (SPSS) 16.00 for Windows. Results: There are 84 subjects eligible for the criteria. Asphyxia (p= 0.121) and premature (p= 0.393) are not risk factor for epilepsy. Hereditary factor (p= 0.001), complex febrile seizure (p= 0.000), and head trauma history (p= 0.001) are significant risk factor for epilepsy. Logistic regression result shows that the risk factors affecting epilepsy in children at Dr. Moewardi Hospital were complex febrile seizure (OR= 18.267 ; Cl 95% 5.393 s.d. 61.873 ; p= 0.000) and head trauma history (OR= 16.341 ; Cl 95% 3.346 s.d. 79.801 ; p= 0.001). Conclusions: Risk factor of epilepsy in children are complex febrile seizure and head trauma history. Keywords: hereditary, asphyxia, premature, complex febrile seizure, head trauma history, children with epilepsy